Mohammad Sjafei's Educational Philosophy from an Axiological Perspective - Sunarti, Vevi; Anita Wati, Listia (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
This research aims to describe Mohammad Sjafei's educational thinking from an axiological perspective in the philosophy of science. This study falls under the category of literature review and employs an interpretative-descriptive method. The author conducted a literature study to gather sources, then utilized relevant sources for the interpretation process, followed by presenting the interpretation results in well-structured sentences. The research findings depict Mohammad Sjafei as a national educational figure who has formulated educational concepts embodying values of freedom, character, ethics, and religiosity. Sjafei agrees with Dewey's notion that the pattern of education through learning and working will shape character, social sense, and mutual assistance. Students are taught tasks aligned with their talents and interests to prepare them for the future, with the hope of nurturing independent Indonesian youths.Keywords: Axiological, Philosophy of Science, Ethics, Religiosity.